(untitled) (Eurasian Journal of Humanities and Social Sciences, 2022)
This article also analyzes various discussions about the types of incentives in the public service. In addition, the article analyzes the framework established by law for the frequency of assessing the effectiveness of the professional activities of civil servants, the appointment of measures to encourage civil servants and the possibility of their subsequent application. This article analyzes the theoretical and legal foundations of the types of incentives in the public service.